STARD 13 in prostate cancer. (c2018) - Saab, Sahar S. (2018)
Prostate cancer is the most commonly diagnosed solid organ tumor and one of the main leading causes of death – due to cancerous tumors- among men in the world. Malignancy of a tumor is characterized by the rapid and uncontrolled growth and its ability to metastasize. Proliferation and migration are known to be regulated by Rho family of GTPases. StarD13 is a GAP for Rho GTPases and has been previously described to be a tumor suppressor in astrocytoma, breast and colorectal cancer. In this study, we investigate the role of StarD13, an inhibitor of RhoA and Cdc42 through its GAP activity, on prostate cancer cells proliferation and metastasis by manipulating its level of expression in the cells. Knocking down StarD13 by siRNA led to an increase in cell proliferation and adhesion yet a decrease in cell motility and cell speed in prostate cancer. The activation levels of CDC42 following StarD13 knockdown are also being investigated through FRET. Our data showed that StarD13 knockdown had no significant effect on prostate cancer cell invasion; further investigations are to be accomplished in order to discover the reasons behind this insignificance.